2004
DOI: 10.1128/jb.186.4.978-988.2004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Structural Characterization of the Core Region of the Lipopolysaccharide from Serratia marcescens N28b (Serovar O4)

Abstract: The gene cluster (waa) involved in Serratia marcescens -Glc-(136)-␣-Glc-(134))-␣-D-GlcN-(134)-␣-D-GalA-[(241)-␣-D,D-Hep-(241)-␣-Hep]-(133)-␣-L,D-Hep[(741)-␣-L,D-Hep]-(133)-␣-L,D-Hep-[(441)-␤-D-Glc]-(135)-Kdo.The D configuration of the ␤-Glc, ␣-GclN, and ␣-GalA residues was deduced from genetic data and thus is tentative. Furthermore, other oligosaccharides were identified by ion cyclotron resonance-Fourier-transformed electrospray ionization mass spectrometry, which presumably contained in addition one residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Thus, it is predicted that these strains contain wabG, wabH, and wabN homologues. This has been shown for S. marcescens N28b where these gene homologues are able to complement the corresponding K. pneumoniae mutants as shown in this and previous work (7,11,17). Interestingly these three genes are also found as predicted in P. mirabilis HI4320 (pedant.gsf.de/cgi-bin/wwwfly.pl?SetϭProteus_mirabilis& Pageϭindex).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Thus, it is predicted that these strains contain wabG, wabH, and wabN homologues. This has been shown for S. marcescens N28b where these gene homologues are able to complement the corresponding K. pneumoniae mutants as shown in this and previous work (7,11,17). Interestingly these three genes are also found as predicted in P. mirabilis HI4320 (pedant.gsf.de/cgi-bin/wwwfly.pl?SetϭProteus_mirabilis& Pageϭindex).…”
Section: Discussionsupporting
confidence: 80%
“…The K. pneumoniae outer core disaccharide ␣GlcN-(1,4)-␣GalA linked by an ␣1,3 bond to LD-HeppII is also found in S. marcescens (17); P. mirabilis serovars O3/S1959, R110/1959, and OXK; Proteus vulgaris O25; and Proteus penneri strains 37 and 34 (for a review, see Ref. 30).…”
Section: Discussionmentioning
confidence: 99%
“…11). This common fragment is also found in the core LPS of Klebsiella pneumoniae and Serratia marcescens (12)(13)(14), and we have shown that two enzymes are required for the incorporation of GlcN into the core LPS of K. pneumoniae: the WabH enzyme catalyzing the incorporation of GlcNAc from UDP-GlcNAc to outer core LPS and WabN catalyzing the deacetylation of the incorporated GlcNAc (15). The rest of the Proteus core OS is quite variable, with up to 37 different structures recognized in the genus Proteus and 11 in P. mirabilis (11).…”
mentioning
confidence: 86%
“…P. mirabilis core OS structures and genetic organization of the core OS biosynthetic clusters. A, the common part of core OS shared by all of the studied strains of P. mirabilis (11), K. pneumoniae, and S. marcescens (11,13,14). Broken lines denote the truncation level for the different core biosynthetic gene mutations (13,14,15,16,35).…”
Section: P Mirabilis Wa Genementioning
confidence: 99%
“…The resulting molecule serves as an acceptor for the transfer of the first heptose residue to position 5 of the first Kdo residue, which is accomplished by the heptosyltransferase I WaaC (14,31). Heptosyltransferase I genes in Salmonella enterica, Escherichia coli, Klebsiella pneumoniae (29), and Serratia marcescens (8,9,31), as well as genes in Pseudomonas aeruginosa (11), Neisseria spp. (32,39), Campylobacter spp.…”
mentioning
confidence: 99%